MIGRAINE: A POSSIBLE CAUSE FOR COGNITIVE DECLINE - Kn, Poornima; N, Karthick; Sadasivam, Kanimozhi; Shivasekar, Meera; Shanmugam, Sundar; D, Balakrishnan; A, Saravanan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives:Migraine is the second most common type of headache and seventh most disabling disease worldwide. In general, obesity is often related to headache disorders in several clinical and epidemiologic studies. Obese migraine patients may have an increased attack frequency due to increase in inflammatory response. Cognitive decline is the major pitfall of migraine disorder and there exists a conflicting result between cognition and migraine and the effect of Body Mass Index (BMI) on migraine. So this study is done to find out the relationship between cognition and migraine and its association with BMI. Methods:The study protocol was approved by the ethical committee of SRM Medical College Hospital & Research Centre. The study group consisted of 30 migraine patients and 30 healthy controls aged between 18-40 years of age. Informed consent was obtained from all the participants. Diagnosis of migraine was made using the criteria of 2nd edition of International Headache Classification (IHC). Patients affected by Diabetes mellitus, Hypertension, allergy, inflammation, infection or immune disorders were excluded. Height and weight of the subjects were taken to calculate the BMI. Cognitive tests such as stroop interference trial & trial making tests (A&B) were done to evaluate working memory, mental flexibility and attention. Results:Compared to controls, cases took more time for performing stroop colour card test (106.40 ± 15.87 seconds vs. 132.17±7.027seconds, p<0.001) and trial making pattern B (54.77± 8.169 seconds vs. 56.23 ± 23.457seconds, p=0.004). Among the migraine subjects, obese individuals had an increased frequency of migraine attack per month (Correlation coefficient r=0.797) Conclusion:Cognitive decline in migraine is one of the underestimated problems in migraine. Identifying such problems early can prevent major consequences in day to day activities of migraine patients. Since there is an increased frequency of migraine with increase in BMI, obese migraine subjects can be recommended to do regular exercises.